Cassava-based (Manihot esculenta Crantz) fermented energy-protein food for bovines (Agro Productividad, 2022)
LObjective: To assess the effect of different yeast levels and fermentation times on the chemical, fermentative, and microbiological composition of cassava in order to produce a cassava-based fermented food.Design/Methodology/Approach: We used a completely randomized design with a factorial arrangement, three yeast inoculum levels (0, 5, and 10%), and five fermentation times (0, 1, 2, 3, and 4 days).Results: We found significant interaction of the studied factors with the pH and crude protein (CP) variables. The highest pH values were obtained adding 10% yeast inoculum (YI) (8.67). CP values of 16.55% were found. No differences caused by the studied inoculum levels and fermentation times were found in true protein (TP) and the in situ degradation of dry matter (IDDM). TP and IDDM had 8% and 80% values, respectively.Study Limitations/Implications: A behavior test with bovines must be conducted to demonstrate the potential of cassava-based fermented foods in meat and/or milk production.Findings/Conclusions: The yeast inoculum and the fermentation days did not increase the TP in the cassava-based fermented food.